Comparative approach on load balancing algorithm by partitioning of public cloud (International Journal of Engineering and Computer Science, 2014)
Load Balancing Concept  in cloud computing has an significant effect on the performance, If load balancing is not done then  numerous drawbacks occurs. As there are tremendous increase in  traditional use of internet due to which uneven distribution of work load can occur then can cause some server overloaded and other under loaded, which can cause server crash. The efficiency of cloud computing can be increased by the technique provided here. This paper introduces an improved load balancing model for the cloud partition on cloud. In this paper a comparative study of  an Ant colony and Honey Bee algorithm is done  to check the best load balancing  technique. The system has  main controller chooses  the suitable balancer for the incoming job. The balancer further selects the server based on the two algorithm(Ant Colony or Honey Bee). Hence, this system will help to select an optimal balancer and the subsystem(server) to allocate jobs (data).